KETERASINGAN SOSIAL SEBAGAI FAKTOR PEMICU PENYALAHGUNAAN NARKOBA DI KALANGAN REMAJA - Ciek Julyati Hisyam; Alif Aditya; Davina Az-Zahra; Dimas Galih; Fadhilatus Sholihah; Mayyaza Nafilata; Syifa El Sahla (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2025)
The phenomenon of drug abuse among teenagers has become a serious concern in Indonesia. This research discusses social alienation as one of the main factors triggering such behavior. Using the approaches of Differential Association Theory, Anomie, and Social Control, as well as descriptive qualitative methods, this research explores how social isolation, anomie pressure, and weak social control can act as catalysts for drug use among adolescents. The results show that social isolation increases the risk of negative influences from unhealthy environments, such as friendships involved in drug use. This research recommends community-based intervention strategies to address this issue.